Selective Hydrogen Generation from Formic Acid with Well‐Defined Complexes of Ruthenium and Phosphorus–Nitrogen PN3‐Pincer Ligand. Issue 9 (21st April 2016) - Pan, Yupeng; Pan, Cheng‐Ling; Zhang, Yufan; Li, Huaifeng; Min, Shixiong; Guo, Xunmun; Zheng, Bin; Chen, Hailong; Anders, Addison; Lai, Zhiping; Zheng, Junrong; Huang, Kuo‐Wei
Abstract: An unsymmetrically protonated PN 3 ‐pincer complex in which ruthenium is coordinated by one nitrogen and two phosphorus atoms was employed for the selective generation of hydrogen from formic acid. Mechanistic studies suggest that the imine arm participates in the formic acid activation/deprotonation step. A long life time of 150 h with a turnover number over 1 million was achieved. Abstract : Grabbing hold : A PN 3 ‐pincer complex was employed for the selective hydrogen generation from formic acid. Mechanistic studies suggest the imine arm participates in the formic acid activation/deprotonation step. A long life time of 150 h with a turnover number over 1 million was achieved.